2003
DOI: 10.1007/s00296-003-0303-6
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, autoimmune, and clinical profiles of patients with systemic lupus erythematosus in Oman

Abstract: Seventy female and three male Omani systemic lupus erythematosus (SLE) patients are described. At disease onset, 45 (62%) were under 20 years of age, and the remainder were between 20 and 44. Of all cases, 48% were familial. Over 5 years, the cumulative frequencies of autoantibodies was: antinuclear antibodies (ANA) 97%, anti-double-stranded DNA (anti-dsDNA) antibodies 92%, extractable nuclear antigen (ENA) antibodies 64%, antineutrophil cytoplasmic antibodies (ANCA) 58%, antiphospholipid (APL) antibodies 80%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
18
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 27 publications
17
18
2
Order By: Relevance
“…This study was conducted in a tertiary care centre, SQUH and showed that most patients were females of child bearing age and that the majority lived in highly populated governates, Al-Batinah and Muscat. The cumulative frequency of haematological and inflammatory markers from the present study was similar to those from Al-Maini M 2003 1 . Both studies showed that the majority of SLE patients were anaemic, lymphopenic and had a high erythrocyte sedimentation rate and hypo-complimentemia.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This study was conducted in a tertiary care centre, SQUH and showed that most patients were females of child bearing age and that the majority lived in highly populated governates, Al-Batinah and Muscat. The cumulative frequency of haematological and inflammatory markers from the present study was similar to those from Al-Maini M 2003 1 . Both studies showed that the majority of SLE patients were anaemic, lymphopenic and had a high erythrocyte sedimentation rate and hypo-complimentemia.…”
Section: Discussionsupporting
confidence: 85%
“…Systemic lupus Erythematosus (SLE) belongs to a spectrum of autoimmune disorders. It is a multisystem disease and it is affected by genetic, ethnic and environmental factors as shown in previous studies 1 . The disease severity and organ involvement vary throughout the world which reflect the multi factorial causes and triggers of the disease 2,3 .…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…This is a very interesting result, being remarkably higher than any other result reported so far. However, the positive ratio of the anti-Sm was 50% in the Omani SLE in 2003 in the report of Al-Maini and colleagues [2], and this was similar to the result of neighboring nations. In their report, the number of object patients was more than that in Al-Jabri's report.…”
supporting
confidence: 83%